Efficacy and safety of three species of Rhodiola L. in patients with chronic obstructive pulmonary disease: A systematic review and meta-analysis - Yu, Haichuan; Lei, Ting; Su, Xiaojie; Zhang, Lu; Feng, Zhouzhou; Dong, Mengya; Hou, Zheyu; Guo, Hong; Liu, Jian (Frontiers in Pharmacology, 2023)
Background: Chronic obstructive pulmonary disease (COPD) is characterized by chronic hypoxia, inflammation, oxidative stress, and irreversible airflow limitation. Rhodiola L. is a genus of botanical drugs that came from traditional medicine and was thought might have an effect on COPD. Objective: Exploring the safety and efficacy of Rhodiola L. in patients with COPD by a systematic review. Material and Methods: In this study, we searched PubMed, Embase, Cochrane Library, Web of Science, Scopus, China national knowledge infrastructure(CNKI), Chongqing VIP database, Wanfang database, and Sinomed database. The search strategy was built using terms including "COPD" and "Rhodiola", etc. Literature screening, data extraction, and risk of bias assessment were conducted by two independent reviewers, and a third reviewer was involved to resolve disagreements. Statistical analysis was conducted in Review Manager (version 5.4.1) following Cochrane Handbook. Results: Nine studies were included in this study, of which two focused on Rhodiola crenulata (Hook.f. & Thomson) H.Ohba(R. crenulata) and two on Rhodiola kirilowii (Regel) Maxim (R. kirilowii), and the rest five on Rhodiola wallichiana (Hook.) S.H.Fu (R. wallichiana). Compared with the placebo, patients who received Rhodiola L. presented no more adverse events(p = 0.65), but significant improvement in the percentage of forced expiratory volume in 1 second at prediction (FEV1%pred), forced expiratory volume in 1 second (FEV1), the ratio of forced expiratory volume in 1 second on forced vital capacity (FEV1/FVC), a saturation of oxygen in arterial blood, partial pressure of oxygen in arterial blood (PaO2), partial pressure of carbon dioxide in arterial blood (PaCO2), systolic pulmonary arterial pressure, diastolic pulmonary arterial pressure, COPD assessment test, efficient rate, C reactive protein, N terminal pro B type natriuretic peptide (all p < 0.01). Compared with ambroxol, R. kirilowii brings additional benefits to patients with COPD in FEV1%pred, FEV1, FEV1/FVC, PaO2, PaCO2, 8-iso-prostaglandin F2α, superoxide dismutase, glutathione, malondialdehyde, total antioxidant capacity (all p < 0.01). Conclusion: In the Rhodiola L. genus, R. wallichiana, R. crenulata, and R. kirilowii were included in this study, and might be safe and effective in COPD. While limitations exist in this study, further RCTs are still in need.